k-6/2=2

Simple and best practice solution for k-6/2=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-6/2=2 equation:



k-6/2=2
We move all terms to the left:
k-6/2-(2)=0
determiningTheFunctionDomain k-2-6/2=0
We add all the numbers together, and all the variables
k-5=0
We move all terms containing k to the left, all other terms to the right
k=5

See similar equations:

| 23=x/9+5 | | 1/9-4x=9 | | 2/3x-9=18 | | 18x^2-57x-60=0 | | 8(x+2)+6=4x+4(5+x) | | (9x+1)^2=36 | | 5=√√(x-2) | | 9x-(5x-13)=45 | | 6+2=-2(8x-4) | | 7-3x=-4x-13 | | x=x/9x-7 | | -4(2+4)=9-3z | | x-2(3x+6)=6-5x | | -3(x+6)-(3x-7)=-7x | | 5x+8=2x+22 | | 1/3x-6=-2/3x-8 | | -4z-6z=-2z+2-3z | | X/3x-9/x=1/2 | | 3t+16=t+412+t−212 | | j/3-10=-6 | | 2/3y+3/2=-1/12y | | 49x=180 | | 1+20=-3(6x-7) | | 34×3a=-7(1+a)+1 | | 12/3x=24 | | 4(5-p=8 | | -5(2w+11)=25 | | 2(7.5)-3c=1.5 | | 4(-3x+1)=11(x+1) | | -9x2+15x-4=0 | | 5p+2=-10p | | 5/7x+6=-2/7x+6 |

Equations solver categories